THE IMPACT OF FOREIGN DEBT ON EXPORT AND IMPORT VALUES, THE RUPIAH EXCHANGE RATE, AND THE INFLATION RATE - Murfani Umar Djalo; Muhammad Yusuf; Juliani Pudjowati (Jurnal Ekonomi, 2023)
Before Indonesia entered the reform era, Indonesia was in the New Order system, which many people considered the system in this era to be too authoritarian. This study aims to determine the effect of the value of exports, imports, the rupiah exchange rate and the inflation rate on foreign debt after the reform era. This type of research uses quantitative methods which are methods that use mathematical models, calculations, statistics and tables. This study uses Indonesia as the object of research using data from 1998 to 2021. Data is collected quarterly or every three months of the year taken from various sources, namely the Central Bureau of Statistics (BPS) and Bank Indonesia. The research method uses the Multiple Linear Regression method. The results of the study simultaneously, all of the independent variables X1 (exports), X2 (imports), X3 (exchange rates) and X4 (inflation) have the same or simultaneous and significant effect on variable Y (foreign debt) with a calculated F value ( 4.97) > F table (2.30) and significance (0.0011) < 0.05. All independent variables are also able to explain the model by 17.9%, as shown by the R-Squared value of 0.1794. Partially, variables X1 (exports), X2 (imports), X3 (exchange rates) and X4 (inflation) have no effect on variable Y (foreign debt) in Indonesia after the reform era.